Building Bridges Through Meaningful Occupation - Jennifer Fortuna (Scholarworks @ WMU, 2017)
Mary Block, MS, OTR/L, an occupational therapist and artist based in Illinois, provided the cover art for the Summer 2017 issue of The Open Journal of Occupational Therapy (OJOT). Generations is a sculpture made from concrete that measures 240 x100 in. (6.096 x 2.54 m). The piece was commissioned by Mary's home town, the Village of Deerfield, IL. Mary always knew she wanted to be an artist. When competing paradigms altered Mary's career path, the field of occupational therapy helped her to shape a new worldview. In uncertain times, meaningful occupation empowered Mary to start over again where she originally began